Pengaruh Persepsi Kebermanfaatan, Kemudahan Dan Keamanan Terkait Uang Elektronik Terhadap Kepuasan Penggunaan E-Money (Studi Pada Pengguna Jasa Transportasi Laut Ketapang-Gilimanuk) - Laila, Nur; Herawati, Nyoman Trisna (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
AbstractThis research was conducted to examine the effect of perceptions of usefulness, easy of use and security related to electronic paymentÂ  on e-money usage satisfaction and the effect of the three variables on e-money usage satisfaction. This type of research is quantitative research, where this research collects, processes, presents, and analyzes data quantitatively (numbers) and descriptively (sentence descriptions). This research was conducted at the Ketapang-Gilimanuk port in Jembarana district, Bali. The subject of this research is users of sea transportation services because ship users are definitely using e-money. The sampling technique used accidental sampling, namely the sampling technique based on chance, and obtained as many as 97 respondents. The research data were collected using a questionnaire which was then processed using multiple linear analysis tests with the help of SPSS version 24. The results showed that the perceived usefulness variable (X1) had a positive and significant effect on the use of e-money. The easy of use variable (X2) has a positive and significant effect on the use of e-money. The satisfaction variable (X3) has a positive and significant effect on the use of e-money. And finally, the perception of usefulness, easy of use, and satisfaction variables together has a positive and significant effect on the use of e-money.Â